2015
DOI: 10.5807/kjohn.2015.24.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychosocial Work Environment on Stress, Depression, Sleep Disorder, and Burnout of General Hospital Nurses

Abstract: The purpose of this study was to assess the psychosocial work environment of hospital nurses to identify influences of psychosocial work environment on stress, depression, sleep disorder, and burnout. Methods: A total of 219 nurses working in one hospital were surveyed by using the Korean version of the Copenhagen Psychosocial Questionnaire (COPSOQ-K) mental health and psychosocial work environment. The impact of the psychosocial work environment on mental health was analyzed using multiple regression. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
3
2
0
1
Order By: Relevance
“…Among the work characteristics, “workload” and “emotional work demands” were the significant factors influencing sleep disturbance, which increased the odds of sleep disturbance by 1–3%, as one unit of workload as well as emotional work demands increased on a 0–100 scale. These findings were consistent with a previous study that identified a significant association between workload, emotional demands, and sleep disturbance in hospital nurses in France [ 29 ] and Korea [ 30 ], and wage workers in Sweden [ 31 ] and France [ 32 ]. As high work demands are a typical workplace stressor [ 33 ], resulting in increased activity of the sympathetic nervous system and subsequent sleep disturbance [ 13 , 34 ], it is necessary to adjust unfavorable work demands to improve sleep disturbance in night-shift workers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the work characteristics, “workload” and “emotional work demands” were the significant factors influencing sleep disturbance, which increased the odds of sleep disturbance by 1–3%, as one unit of workload as well as emotional work demands increased on a 0–100 scale. These findings were consistent with a previous study that identified a significant association between workload, emotional demands, and sleep disturbance in hospital nurses in France [ 29 ] and Korea [ 30 ], and wage workers in Sweden [ 31 ] and France [ 32 ]. As high work demands are a typical workplace stressor [ 33 ], resulting in increased activity of the sympathetic nervous system and subsequent sleep disturbance [ 13 , 34 ], it is necessary to adjust unfavorable work demands to improve sleep disturbance in night-shift workers.…”
Section: Discussionsupporting
confidence: 93%
“…Social support and communication did not have a significant influence on sleep disturbance. This was in agreement with a previous study on hospital nurses in Korea, in which social support from colleagues or supervisors, and trust and justice at the workplace did not influence sleeping troubles [ 30 ]. Although further investigation is needed to identify discrepancies in the influence of social support and communication on sleep disturbance, it seems that social support and communication might have an indirect rather than a direct influence on sleep disturbance among all wage workers [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, among the covariates, sleep quality was a factor associated with both stress and depressive symptoms, and 60.1% of the IBS group self-reported that their sleep quality was poor, indicating that nurses with IBS experience sleep problems. According to Lee and Choi [ 20 ], nurses had higher levels of stress and depressive symptoms than other occupational groups, and the stress and depressive symptoms of nurses were associated with sleep disturbances. The high prevalence of IBS observed in rotating shift workers could indicate a relationship between IBS and circadian rhythm disturbance [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are at a higher than average risk of developing IBS due to the irregular life rhythms and sleep problems associated with shift work [ 19 ]. Nurses are also one of the occupational groups with high levels of stress and depressive symptoms [ 20 , 21 , 22 ]. To safeguard the psychological health of nurses with IBS, it is necessary to examine the relationship between IBS and stress and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…, 가족이나 간병인 간호보다 만 족도가 10% 상승한 것으로 나타났다 (Kwaks, 2015) (Lee, Yoon, & Lee, 2012;Yoon & Kim, 2013), 미 국의 경우 약 34% (Welsh, 2009) (Welsh, 2009)과 정신 ․ 심리적 측면의 직무 스 트레스 (Welsh, 2009), 직무소진 (Lee & Choi, 2015) (Lee, 2016;Lee & Jung, 2015), 감정노동 (Im, 2015), 직무소진 (Im, 2015), 이직의 도 (Im, 2015;Lee, 2016) (Shin & Kang, 2011), 중등도 이 상의 감정노동수행 (Shin & Kang, 2011) 및 직무소진 (Kim & Lee, 2014) 등으로 인해 신체증상을 경험하고 있다 (Kim & Lee, 2014;Shin & Kang, 2011;van der Doef, Mbazzi, & Verhoeven, 2012). 특히 교대근무간호사는 두통, 불면, 과다 주간 졸리 움, 불안 및 우울 등의 신체증상을 경험하는 것으로 보고되고 있다 (Kim, Choi, Kim, Kim, & Eun, 2014 (Lee & Lee, 2011)과의 관련성 및 감정노동 (Im, 2015;Lee & Lee, 2011), 직무 스트레스 (Im, 2015), 직무소진 (Im, 2015;Lee & Lee, 2011)…”
unclassified